Output Decline and Recovery in Uzbekistan : Past Performance and Future Prospects - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper, 1998)
What explains Uzbekistan's unusually mild 'transformational recession' and its moderate recovery during 1996-97? We examine potential biases in output measurement, the role of 'special factors'-including initial production structure, natural resources, and public investment policies-and sectoral output developments. The main findings are (i) Uzbekistan's relatively favorable output record is not an artifact of measurement alone; (ii) public investment has had no significant effects on growth; (iii) the mildness of Uzbekistan's transitional recession can be accounted for by its favorable initial production structure and its self-sufficiency in energy; (iv) unless reforms are significantly accelerated, medium-term growth prospects are mediocre.